Chronic Care Model for the Management of Patients with Heart Failure in Primary Care. (August 2019) - Francesconi, Paolo; Ballo, Piercarlo; Profili, Francesco; Policardo, Laura; Roti, Lorenzo; Zuppiroli, Alfredo
We recently investigated the prognostic impact of a Chronic Care Model (CCM)-based healthcare program applied in primary care in Tuscany Region mainly run by multidisciplinary teams composed of general practitioners (GPs) and nurses. The project included proactively planned follow-up visits for each patient, individualized counselling to optimize lifestyle modifications and adherence to appropriate diagnostic and therapeutic pathways. 1761 patients with Chronic heart failure (CHF) directly enrolled by the GPs were matched with 3522 CHF controls not involved in the project. Over a 4-year follow-up in the CCM group a higher CHF hospitalization rate was found (12.1 vs 10.3 events/100 patient-years; incidence rate ratio [IRR] 1.15, p=0.0030), whereas mortality was lower (10.8 vs 12.6 events/100 patient-years; IRR 0.82, p<0.0001). The CCM status was independently associated with a 34% increase in the risk of CHF hospitalization and a 18% reduction in the risk of death (p<0.0001 for both). The CCM status was associated with a 50% increase in the rate of planned Heart failure (HF) hospitalizations whereas the rate of 1-month CHF readmissions showed no differences. Such a divergent trend could be explained by the direct involvement of GPs in the CCM program, leading them to a better awareness of patients' clinical status, and then to a more frequent use of clinical pathways and facilities, including hospitalization. It is reasonable to argue that not all hospitalizations must necessarily be considered as a poor outcome, as they often provide additional opportunities to improve therapies, optimize patient education, or define follow-up strategies. The evidence of a divergent trend between mortality and hospitalization in our population might support the clinical importance of a multidisciplinary approach for the management of patients with HF.